Small Signal Stability Assessment in Presence of SSSC for a Power System Under Fault Disturbance - Rupali Brahmachary; Dipu Sarkar (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2021)
The use of FACTS controllers in power grids has resulted in the improvement of stability issues related to the power systems. When the FACTS controllers are used to damp out the power systems oscillation, there series controller inverter like static synchronous series compensator (SSSC) device are the most suitable to resolve the issue. In this paper, importance is given on the optimal operation of the SSSC and to the maintenance of the small signal stability of the system. Here the main focus is to check the system response to stability after the use of SSSC device.